2019
DOI: 10.31234/osf.io/4p9zs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De-Rationalising Delusions

Abstract: Due to the traditional conceptualisation of delusion as ‘irrational belief’, cognitive models of delusions largely focus on impairments to domain-general reasoning. Nevertheless, current rationality-impairment models do not account for the fact that i) equivalently irrational beliefs can be induced through adaptive social cognitive processes, reflecting social integration rather than impairment; ii) delusions are overwhelmingly socially-themed; iii) delusions show a reduced sensitivity to social context, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 115 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…The question remains as to what generates the paranoid ideation in the first place. Alterations to coalitional cognitionprocesses involved in group affiliation and social perception-may play an important role here (Bell et al, 2021). Consistent with this idea, Miyazono and Salice (2020) suggest that a failure of group identification may erode or preclude the trust that is typically extended to in-group members.…”
Section: Testimonial Abnormalitiesmentioning
confidence: 82%
See 1 more Smart Citation
“…The question remains as to what generates the paranoid ideation in the first place. Alterations to coalitional cognitionprocesses involved in group affiliation and social perception-may play an important role here (Bell et al, 2021). Consistent with this idea, Miyazono and Salice (2020) suggest that a failure of group identification may erode or preclude the trust that is typically extended to in-group members.…”
Section: Testimonial Abnormalitiesmentioning
confidence: 82%
“…According to Miyazono and Salice (2020), most previous theorizing about delusions-including that reviewed already-has implicated "individualistic sources of evidence" (e.g., perception, reasoning, memory), with less attention paid to how deluded individuals treat social sources (e.g., testimony). To remedy this, Miyazono and Salice advocate a "social epistemological turn" in the study of delusions (see also Bell et al, 2021). In particular, they suggest that testimonial abnormalitiesincluding the active discounting of testimonial evidence ("testimonial discount")-figure in the etiology of delusions.…”
Section: Testimonial Abnormalitiesmentioning
confidence: 99%
“…Previous research has shown that individuals diagnosed with schizophrenia show increased metacognitive confidence for inaccurate beliefs about others during strategic interactions (Joyce, 2013) and for inaccurate perception of self-referential communication (White, Borgan, Ralley, & Shergill, 2016). This suggests that alterations to metacognition for social judgements may play a role in the generation or maintenance of psychotic symptoms (Raihani and Bell 2019) (Bell et al, 2020) echoing recent work on the role of beliefs as having primarily a social function (Williams, 2020). Nevertheless, the extent to which this is characteristic of all people with schizophrenia and / or psychosis has been debated in light of results that suggest that extreme overconfidence for social cognitive judgements was characteristic of only a subset of patients (Jones et al, 2020) which may be one factor in the low strength of evidence for clear effects reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Raihani & Bell, 2017). Notably, psychosis frequently includes the experience of being influenced by outside, often illusory social agents (Bell et al, 2017), and people affected by delusional beliefs can find it hard to withhold communicating their confidence in the belief even when it may lead to social sanction (Bell, Raihani, & Wilkinson, 2020). This suggests that an alteration to the meta-cognitive processes for social influence may be involved in these experiences in psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Paranoia can be highly distressing and, at the upper extremity of the paranoia continuum, forms a core part of psychosis [6]. It is clear that conspiracy beliefs are common in people with paranoid delusions [23] and one distinguishing feature may be that, as paranoia becomes more delusional, concerns about conspiracies are more likely to involve the believer rather than simply focusing on 'significant social and political events' [24]. This suggests that perception of conspiracies and the type of conspiracy may change as paranoia becomes more severe.…”
Section: Introductionmentioning
confidence: 99%